2012
DOI: 10.4162/nrp.2012.6.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the protein expression of transcription factors related adipocyte differentiation and the activity of matrix metalloproteinase in mouse fibroblast 3T3-L1 preadipocytes

Abstract: This study attempted to investigate the effects of resveratrol on the differentiation of adipocytes. After cells were treated with various concentrations of resveratrol (0, 10, 20, and 40 µmol/L), adipocyte proliferation, the protein expression of transcription factors, and MMPs' activities were determined. Cell proliferation was inhibited more within 4 days of incubation (P < 0.05), and lipid accumulation in adipocyte was significantly inhibited by 93.8%, 92.4% and 91.5%, respectively, after two days of 10, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Maiti and Chatterjee [20] reported that GSH also stimulated the arsenic detoxification processes by modulating arsenic methylation and increasing hepatobiliary excretion of arsenic. Resveratrol is a naturally occurring stilbene, a potent free radical scavenger and may also stimulate endogenous antioxidant enzyme activities [21,22]. As expected, As2O3 treatment resulted in significant nephrotoxicity in rats, and pre-treatment with resveratrol attenuated or prevented the oxidative stress, thereby mitigating the subsequent renal damage.…”
Section: Discussionmentioning
confidence: 62%
“…Maiti and Chatterjee [20] reported that GSH also stimulated the arsenic detoxification processes by modulating arsenic methylation and increasing hepatobiliary excretion of arsenic. Resveratrol is a naturally occurring stilbene, a potent free radical scavenger and may also stimulate endogenous antioxidant enzyme activities [21,22]. As expected, As2O3 treatment resulted in significant nephrotoxicity in rats, and pre-treatment with resveratrol attenuated or prevented the oxidative stress, thereby mitigating the subsequent renal damage.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have shown that resveratrol may be involved in the regulation of MMP-2 and MMP-9 activity [22,23] . Gao et al [22] showed that resveratrol reduced the elevated level of MMP-9 induced by cerebral ischaemia-reperfusion in mice, and Kang et al [23] demonstrated that the activity of MMP-2 and MMP-9 decreased significantly at different resveratrol concentrations, with MMP-9 being more significantly affected than MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [21] reported changes in expression of TGF-β1 and MMP-9 in the formation of TS. In addition, several studies have reported that resveratrol affects MMP activity in adipose and neuronal tissues [22,23] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, resveratrol has been shown to be a pro-apoptotic compound against melanoma [219], inducing apoptosis once it induces G1/S cell cycle arrest [27, 220223], through expression of dihydronicotinamide riboside quinone reductase 2 and p53 [221], upregulation of cyclins A, E, and B1 [223], suppression of STAT-3/β-catenin-pathway [224], and production of NO, which stimulates p53 and Bax-Bcl2 mitochondrial apoptosis [225, 226]. Subsequently, cytochrome C, and caspase-9 and -3 are released [227, 228].…”
Section: Resveratrolmentioning
confidence: 99%